Springtime bromine activation over coastal and inland arctic snowpacks - Peterson, Peter K.; Pöhler, Denis; Frieß, Udo (ACS earth and space chemistry, 2018)
With the return of sunlight in the polar spring, the snowpack serves as an effective source of molecular halogens to the Arctic boundary layer. Reactive bromine production and associated ozone depletion are typically associated with sea ice regions; however, the extent to which halogen chemistry occurs inland in coastal regions is unknown. During the March 2012 bromine, ozone, and mercury experiment (BROMEX), airborne nadir scanning differential optical absorption spectroscopy probed the spatial distribution of BrO over sea ice and tundra regions near Utqiaġvik, Alaska. We observed enhanced BrO lower tropospheric vertical column densities (LT-VCDs) up to 200 km inland. Vertical profiles showed that BrO was located near the snowpack surface, consistent with prior studies of snowpack chemical composition showing bromide enrichment, which is indicative of deposition of gas-phase bromine species to the snowpack. Over nine flights across the Alaskan Arctic, the highest BrO LT-VCDs were observed over snow-covered tundra regions rather than sea ice regions, although the variability was large at all locations. Characterization of the response of observed BrO over northern Alaska to ozone conditions at Utqiaġvik showed that regional BrO levels were highest during times when ozone mole fractions were decreasing, consistent with locally occurring chemical destruction of ozone by bromine chemistry. These findings suggest that, while bromine activation is most commonly associated with sea ice regions, inland tundra snowpacks enable the transport and recycling of reactive bromine, extending this halogen chemistry and its associated impacts further inland.
Gesehen am 21.04.2020